1990
DOI: 10.1111/j.1526-4610.1990.hed3004232.x
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Study of Chronic or Recurrent Headache in Systemic Lupus Erythematosus

Abstract: This study was conducted to analyze the prevalence and features of chronic or recurrent headache in Systemic Lupus Erythematosus (SLE), and also the relationship of such headache with other manifestations of the disease. A total of 76 patients (69 women and 7 men) with a mean age of 40 years (r: 24-74 years) were included. An overall severity index for SLE was applied. Fifty-two patients (68%) presented headache, 27 (52%) being vascular and 25 (48%) muscle contraction type. Headache in general was more frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
1
3

Year Published

1991
1991
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 15 publications
(50 reference statements)
0
19
1
3
Order By: Relevance
“…Our study shows that SLE patients with past history of migraine have higher SLICC‐DI scores than patients without this manifestation. Although most previous controlled studies (1–7) did not find an association between SLE and migraine, we demonstrate that, patients with active migraine had higher disease activity scores than patients without migraine and were therefore more often treated with corticosteroids to control SLE activity than patients without migraine. Both the chronic use of corticosteroids and the presence of SLE flairs are features associated with greater organ damage in SLE patients.…”
Section: Discussioncontrasting
confidence: 71%
“…Our study shows that SLE patients with past history of migraine have higher SLICC‐DI scores than patients without this manifestation. Although most previous controlled studies (1–7) did not find an association between SLE and migraine, we demonstrate that, patients with active migraine had higher disease activity scores than patients without migraine and were therefore more often treated with corticosteroids to control SLE activity than patients without migraine. Both the chronic use of corticosteroids and the presence of SLE flairs are features associated with greater organ damage in SLE patients.…”
Section: Discussioncontrasting
confidence: 71%
“…This could mean that headache in SLE could have a vascular physiopathological mechanism among other different associated mechanisms. Nevertheless, other studies had not found association between headache and Raynaud's phenomenon in patients with SLE (3, 8, 21, 22). This discrepancy could be related to population or study design differences or to searching intensity considering that prevalence of Raynaud's phenomenon varies with the observer's specific questioning of the patient.…”
Section: Discussionmentioning
confidence: 91%
“…Nervous system involvement has been found ranging from 14% to 75% (1, 2). Headache, especially of migraine type, is very common in SLE with reported prevalences as high as 65–70% in some studies (3–5). The impact of migraine on daily life is enormous.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, both studies used SLE as a human brain inflammatory model to explore the vascular hypothesis of migraine pathogenesis, with contradictory results. A large number of papers followed reporting high headache prevalence in SLE ranging from 30% to 65%(3–19). Furthermore, in some studies the headache occurrence has been related to SLE exacerbation (3, 9, 12), Raynaud's phenomenon (19) and anticardiolipin antibodies (19, 20), but not all investigators have agreed (12, 15, 21).…”
mentioning
confidence: 99%